Geoarqueología del oro en la zona minera de Pino del Oro (Zamora) - F. Javier Sánchez-Palencia; Damián Romero; Alejandro Beltrán (Mélanges de la Casa de Velázquez, 2018)
In the Pino del Oro (Zamora) mining area primary gold deposits were worked during the first two centuries of the Roman Empire. Recent research has documented the occupation of the area and the extraction of gold in both the Roman and pre-Roman eras. A number of geo-archaeological prospectings using panning methods have served to clarify the system of detection of such deposits. The research has also produced a number of estimations of the output of the pre-Roman inhabitants of the La Ciguadeña castro, where panning has been documented archaeologically for the first time in the Iberian Peninsula. Also, at the castro of Peñarredonda, whose walls were mortred during the Roman era, a terrace system of agriculture was used, which again highlights the non-sectoral nature of mining activity in the ancient rural economy.